Use of Aldosterone Antagonist to Treat Diarrhea and Hypokalemia of Ogilvie’s Syndrome - Pradhum Ram; Abhinav Goyal; Marvin Lu; Joshua Sloan; William McElhaugh (Case Reports in Gastrointestinal Medicine, 2016)
Ogilvie’s syndrome (OS) is a functional obstruction of the bowel due to an autonomic imbalance. It often presents with diarrhea and is associated with hypokalemia. We present a case of a 70-year-old male who developed severe abdominal distension, watery diarrhea, and persistent hypokalemia status after left hip arthroplasty after suffering from a femoral neck fracture due to a fall and was diagnosed with OS. The persistent hypokalemia was slow to improve despite aggressive repletion because of the high potassium losses in the stool. This is most likely mediated through the increased expression of BK channels in the colonic mucosa. Aldosterone is theorized to have a role in the regulation of BK channels. Spironolactone was subsequently given and resulted in marked improvement of the diarrhea and hypokalemia. Thus, this case suggests a novel therapeutic approach for the treatment of Ogilvie’s syndrome-associated diarrhea and hypokalemia.